Analysis of the Relationship between Realization of Local Revenue (Pad) and Realization of Capital Expenditure with Realization of Maintenance Expenditure in Regency / City Governments in South Kalimantan Province in 2010-2016 - Nugeraha, Eddy Harwan; Adriani, Ade; Hamdani, Hamdani (International Journal of Education, Information Technology, and Others, 2024)
The research "Analysis of the Relationship between Realization of Local Revenue (PAD) and Realization of Capital Expenditure with Realization of Maintenance Expenditure in Local Governments in South Kalimantan Province 2010-2016" discusses the importance of local revenues (PAD) in financing development policies in South Kalimantan Province. The authors found that there is a significant correlation between PAD and capital expenditure, as well as between PAD and maintenance expenditure. This suggests that local governments can improve their financial performance by increasing their PAD, which in turn can lead to better public services and infrastructure. The article also highlights the need for better financial management and transparency in local governments to ensure that public funds are used efficiently and effectively. Overall, the article provides valuable insights into the challenges and opportunities of local revenue generation and expenditure management in South Kalimantan Province